Effect of Bilateral Nasal Packing on Systemic Blood Pressure in Patients Treated with Septoplasty - Ikram Ullah, Salman Ahmed Mangrio, Muhammad Farooq Bhutta, Ashfaq Hussain Rana, Anees Ur Rehman, Maqbool Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The primary aim of this research was to assess the impact of bilateral nasal packing on systolic blood pressure in individuals undergoing septoplasty. Study Design: Retrospective study. Place and Duration: This study was conducted at Hospital Dow International Medical College, Dow University of Health Sciences Karachi and Shahida Islam Medical College, Lodhran during in the period from March, 2022 to August, 2022. Methods:152 patients who had a clinically determined nasal septoplasty were included in this study. Patients in this ranged in age from 18 to 50. The patients were randomly split in two groups. Seventy-six patients were assigned to Group I, where no nasal packing was utilized, and Group II, where conventional anterior nasal packing was applied. One may say that there was a 50/50 split between the two groups. Before to and throughout septoplasty, all patients underwent round-the-clock ambulatory blood pressure monitoring. Statistical analysis was performed on all data using SPSS 24. Results: 90 (59.2%) of the 152 patients were male, and 62 (40.8%) of the patients were female. The patients which were under the age of 30 are 59(38.8 percent) of the total patients, 55 (36.2 percent) were between the ages of 31 and 40, and 38 (25 percent) were above the age of 40.50% of the patients are comprised of rural locale. Study participants in Group II were found to have higher mean blood pressure (p-Value 0.05) following septoplasty therapy than those in Group I (P-Value >0.05). Group II patients had bleeding, vestibulitis, and septal perforations as a result of their nasal packing procedure. Conclusion: The study determined that bilateral nasal packing was linked with the preferment in either systolic or diastolic blood pressure in individuals who had septoplasty treatment. There is no statistical significance change showed up with the patients who did not get nasal packing from the rest of the group. Keywords: Septoplasty, Bilateral Nasal Packing, systemic blood pressure